Patient Satisfaction with Pre-hospital Care - Najla Alasmi, Abdullah Ali Alqahtany, Moeed alshehri, Nawfal Aljerian, Ahmed Alotaibi, Maree Alanazi; Anwar Saad Alqarni, Hassan Gasem Harobi, Ahmed Ali Alghamdi, Ahmed Mohammed Alhamad; Qureshi, Shoeb (International Journal of Innovative Research in Medical Science, 2017)
Background: The prehospital care is based on the knowledge and skills needed for the prevention, diagnosis and management of mild to immediate cases of illness and injury which affects all ages with full undifferentiated categories of physical and behavioral disorders. Aim: is to prioritize patient satisfaction with emergency medical services in some aspects to improve and raise the quality of pre-hospital care. Methodology: Customer satisfaction surveys have been conducted. Result: we determined the answers for all the patients in our 72 sample from the patients admitted in National Guard Hospital either by our EMS or by Red Crescent ambulances. Their age ranged from 18 to 86 and older including males and females. The patient’s opinion about overall treatment, and we divided into five levels of satisfaction: (Excellent, Good, Neutral, bad, and Horrible), 68 patients evaluate excellent on percentage of (94.4%), 1 patient evaluate good on percentage of (1.4%), 2 patients evaluate neutral on percentage of (2.8%), 1 patient evaluate bad on percentage of (1.4%), and non of the patients evaluate horrible. Conclusion: the purpose of this study is to measure the level of satisfaction among patients with pre-hospital care to improve and raise the quality of care, and to identify the factors that influence the patient satisfaction. Researches on patient’s satisfaction in emergency medical services are limited especially in (NGHA) and Red Crescent in Saudi Arabia. In this study the patients evaluate the services that provided by the EMS employees with among the ages, between both of the genders and emergencies.